Assessing the levels and prevalence of public speaking anxiety among Indonesian EFL university students - Muhyidin, Mohammad; Chuquin, Ector Geovanny Pupiales (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Research on speaking anxiety among ESL/EFL students has been documented. However, research on speaking anxiety, particularly in the context of public speaking or oral performance at the higher education level, remains underexplored. This research aims to assess the anxiety levels and prevalence of Indonesian EFL university students in public speaking classes. The study involved undergraduate students enrolled in a public speaking class in the fourth semester of the English department at a university in Kediri, Indonesia. A sample (n=51) completed the distributed speaking anxiety survey questionnaire of the Foreign Language Classroom Anxiety Scale (FLCAS) adapted from Horwitz et al. (1986). The collected data were then statistically analyzed using SPSS. The results show that the EFL university students exhibited varying degrees of anxiety from the lowest to the highest levels: anxious, very relaxed, mildly anxious, and relaxed. The most prevalent anxiety among the EFL university students in public speaking was at a relaxed level. Several factors that affect how much speaking anxiety students feel in English classes include not being interested in the subject, their age, not getting enough practice, and their gender. Findings highlight the need for special support in public speaking classes to assist EFL students in dealing with their anxiety.